1992
DOI: 10.1093/aje/136.7.769
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of the Post-Polio Syndrome

Abstract: A late-onset syndrome, consisting of muscle weakness, muscle pain, and unaccustomed fatigue, has been reported with increasing frequency among former poliomyelitis patients. A population-based cohort of poliomyelitis patients from Allegheny County, Pennsylvania, was traced and surveyed to estimate the prevalence and incidence and to identify determinants of the post-polio syndrome. A questionnaire validated in clinical examinations of 40 cohort members was used in the survey. The prevalence of the post-polio s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
2
13

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(111 citation statements)
references
References 0 publications
5
90
2
13
Order By: Relevance
“…We found that 25.7% of polio survivors developed PPS. In the United States, surveys regarding the frequency of PPS development were conducted by Halstead (1985) 1) and Ramlow (1992) 2) . They used the same PPS definition as we did, and reported a 23.4% and 28.5% frequency of PPS development, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 25.7% of polio survivors developed PPS. In the United States, surveys regarding the frequency of PPS development were conducted by Halstead (1985) 1) and Ramlow (1992) 2) . They used the same PPS definition as we did, and reported a 23.4% and 28.5% frequency of PPS development, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of polio in the United States since the 1980s 1,2) . The frequency of polio manifestations in musculoskeletal disorders is high [3][4][5][6][7][8] , and it is accompanied by various symptoms including respiratory function impairments 9) , dysphagia 10) , sleep disorders 11) , dysuria 12) , and cognitive disorders 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Usually there is a full recovery [30][31][32][33][34]. Muscle power begins to return after several days and continues to improve during the next 12-24 months [30][31][32][33][34].…”
Section: Can Polio Be Treated?mentioning
confidence: 99%
“…Results from various studies have found that the prevalence of joint pain ranges from 42% to 80% (Ramlow et al, 1992), and the prevalence of muscle pain ranges from 38% to 86% (Agre et al, 1989). In a sample of 150 polio survivors, 80% of those surveyed complained of pain (Gawne et al, 2000).…”
Section: Introductionmentioning
confidence: 99%